Hedonic Prices for a Nondurable Good: The Case of Breakfast Cereals - Stanley, Linda R.; Tschirhart, John (The Review of Economics and Statistics, 1991)
Numerous studies have estimated hedonic price functions for durable goods. In this paper we apply the methodology to breakfast cereals, a nondurable good. We employ maximum likelihood to estimate the hedonic price functions using data from three large supermarkets. The price function depends on characteristics that provide tastes, nutrition and convenience to consumers, and the estimates yield insights into pricing policies, consumer preferences and consumer use of information.